Experiential Realization in "Poda Ni Namonangon Ribut" on Mandailing Social Context - Ibnu Ajan Hasibuan; Eddy Setia; Masdiana Lubis (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2020)
This study aims to analyze the function and realization of the meaning contained in the Poda ni Namonangon Ribut as an ancient script text contained in the Ulu Pungkut sub-district, Mandailing Natal district. This study uses a qualitative method with the documentation method in which the data is sourced from the Medan Archeology Agency. Data were analyzed using Systemic Functional Linguistics theory on Ideational Functions and to find metaphors of ideational meaning. The results of this study indicate the distribution of the relational process dominates from Participant, Cirmuntance. The realization of the meaning of the ideational function can be seen in the first, metaphor as a description of the community who want to have offspring, where the aim of Poda is ido napajadi boru "what makes a daughter". In the second, there is a metaphor that explains the word Na sundat realized with the words "Heavy Rain", "Divorce", "Birds perch", "ravine". In the third, shows that Poda has methafora like when the expectation is reached, it is the services of the writer "Shaman”. then when the writer has explained what the ingredients are. Social context of text that has a narrative and the author's conclusion about the solution to the problem of everyone who wants offspring in his family. The tradition of writing with the mandailing script (sumurat) became quite a tradition so that there are ancient texts in the traditional house became the animist beliefs and ideologies which can be seen in Bagas Godang.